Pokémon adventures. Black 2 & White 2. Volume 3 - Kusaka, Hidenori; Turnage, Bryant (Viz Media, LLC, 2021)
Whitley and Blake are trapped in ice in Castelia City, while White searches for Black who's been missing since the Ghetsis battle. The team must unite in order to stop Ghetsis, Colress, and the other members of Team Plasma at the Giant Chasm.